Sigorta şirketlerinde denetim - Gül, Yasemin (My University, 2001)
Foundation of insurance is based on feeling in security nad being is safe according to risks, that is the nature of humanity and the feeling began when human being was born. This security factor facts growth of the insurance companies as time passed and being important associations in economy. The purpose of insurance is removing the harmful results change factor by getting measures. In that case, first component of insurance is feeling in security according to risks that may appear in hole life. Second component is scattering total risks. Insurance companies guarantee the giving insurance guarantee respond to collecting premium. Capital accumulation function of insurance ( fund creating function ) shows the insurance companies' point of view mostly. Insurance is defined in two points of view. First is, insurance gets guard according to probable financial loss by an insurer. Second is, insurance is a tool for collecting in an associated fund contracted paying back now or in the future to insured people from insurer, because of the connected risks of two or more people or companies'. In insurer's point of view, insurance is a keeping nad collecting, that means insurance is an accumulation tool. Insurance companies must use the collected premium suitable to security principle for adapting completely the possible responsibilities that may appear in the future, and as the end of this factor for insured people will not be wronged. Insurance companies must have a strong structure especially about finance and techniques, that's why these conditions will be come true, because of this inspection is very important. Inspection is a systematic process that economical activity and events concerned claim before hand determined criterion for researching the suitability degree nad by the aim of notify the results to the related people who collect the evidence. Inspection, benefits different profit groups arranges economical life in community. In addition, control ; benefits the inspected financial tables credit possibility improve, clarifies to investor's decision, prevents the loss of the goverment tax, increases the reliance of financial tables. Inspection is applied by inspectors. Inspector is devoted himself to the occupation, neutral, has no projedice, objective, hardworking, harmonious to work, quick for finishing work, attentive, tidly, has ability for choosing method, entrepreneur, creative, has cmprehension, has the appraise ability, his spoken nad written expression is well, has ability for work alone or together, has self- confidence, obey the laws and the rules, brave, resolutely, steady, has local worth, successful at people contacts, has convince ability, desiding quickly and correctly, ability in unusual conditions, secretive, thrust worthy, not being addicted to personnel profits. Inspectors may be collected in three groups ; these are, independent inspectors, internal inspectors and public inspectors. Independent inspectors are self employed inspectors and have no organic connection with a person or a company. Self employed emphasize that the inspector is completely independent from the inspected company. Internal controllers are the controllers that are dependent to specific company work inside. Same as the independent inspectors, there is no connection legal laws for internal inspectors. An inspection is applied by internal inspector is connective for the only administration management. That's why the involved laws are settled by administration management. Basic reason of there is no legal preparation about internal inspectors is, result of inspection are not directed towards about clarifying public. That's why, even though inspection results are applied by internal inspectors who are reliable, a third person may suspects about him. Because inspectors are not legal responsible to third person. The public inspectors are the inspection members that inspect in the name of the Government. When an inspection activity is applied, inspection methods are clarified below ; These are ; · Inspection methods with regard to scope · Inspection methods with regard to content · Inspection methods from the point of view of inspection side · Inspection methods with regard to source document Obtaining the kinds of inspection evidence means inspection technique. Work and functions of inspected administration is related to the purpose of inspection with respect to determining in the beginning criteria, rules and principles, standarts or legal arrangement and as the same relation is suitable or not ; if it can show the real position, if it is reliable. They are the functions that are applied for getting the inspection results most quickly and being applied flawless for inspection functions. When the inspector determines the real situation and required, fixing differences, he must apply the inspection techniques, so he prevents the law of time and work power. Actual purpose of inspection techniques is getting adequate and reliable inspection evidence and having enough information for inspection's point of view about inspected administration. Each function in inspection process is based on an inspection technique. Each used inspection technique in inspection area has their own special properties. Inspection techniques for using, are different according to inspection scope, organization structure of administration activity of internal inspection system and inspected departments. The important point is ; inspection techniques are not independent and different from each other. Inspection techniques are verifying, physcial inspecting and counting, inspecting documents, recalculating, inspecting enrollment system, investigation, inspecting one by one and analytical inspection. As for inspection standarts are criterion entireness according to work quality, also it contains inspector and all inspection process from the beginning to the end by its own properties. Inspection standards are departed into 3 parts ; general standards, working area standarts and reporting standards. General standards are according to inspector. One of the most important factors is inspector certainly. Even though the other factors are positive, if the inspector does not have the necessary quality, inspection results will not be reliable and well planned. That's why standards about inspector effect the other standards directly, briefly, general standards certain independence, necessary attention and care factors. Working area standards determine works will be completed in the future, and it determines the inspection activity area. Working area standards, also help for evaluating evidences for having opinion about finacial tables. Working area standards get planning and supervision, determining the internal control system, and must collect anough and reliable evidence. Reporting standards are about the report that inspector prepared at the end of the inspection process. It determines what the inspector has to know about financial and technical activities of inspected administration. Reporting standards are suitable for accounting principles that are accepted in common, unchangeable accounting principles, enough explanation and informing opinion. Insurance companies' inspection in Turkey, are collected in 3 main headlines ; these are public inspection, independent external inspection and internal inspection. There are two areas that must be prepared by law rules at insurance activities. First one is, arranging the character and working of insurance companies that work by insurance activity. Second one is, determining compact decision are dependent to insurance agreement that founds insurance relation. The most important feature of the insurance companies is being dependent to public inspection. In respect to the insurance characteristic is a kind that mostly social active in economical and financial activities. Public inspects the insurance companies, according to need and characteristic of insurance that must be different and special rules. Inspection Insurance Companies are prepared by 3379 numbered law and 7397 numbered different Insurance Inspection Law in Turkey have been Processes about Insurance Contracts arranged by 5th book of Insurance Law of Turkish Commercial Law. The mail purpose of the public inspection of the insurance companies is arranging financial and technical structure of the companies and affording the payment potential to insured people need with respect to insurance that completely related to reliability. That means the mean reason of inspection is protection of insured people rights and benefits. A case must be considered for interference economical activity of public is must be applied convenient to the law base and porpuse interference must damage the other side at least and it must be equal. Public interferes special enterprises in two phase ; these are during foundation and starting, public control and throughout continuation working. Judgement about insurance inspection is seperated into two parts according to their importance : Judgements of first group is related to arranging finacial and technical structure of the companies that will be insurance company. The subject is foundation form of the insurance company, capital quantity and payment form, need, and determinig the departed guarantee limiting usage of active quantity, and on the other hand inspection of applied rules for the future that will be used for fixing tariff is under consideration. Judgement of the second part is finding and fixing of the insurance conditions contract for poor people about economy against the insurer compact, in this group there are general conditions and application may be done after the public inspection. Public interferes the insurance companies in two steps ; Fist one is some conditions that appear in foundation process. These conditions from legal obligation of public inspection. Second one is, the conditions that the insurance companies must obey. These conditions are financial obligation. Legal preparation about inspection of insurance companies in Turkey is departed into different laws. These are ; Law, Regulations, General Insurance Rules and Law Court Decisions. We may notify the external inspection insurance companies are in systematic process collecting evidence in neutrality for correcting the degree of criteria suitability was determined before, evaluating these evidences and having purpose of transferred the results to the related users. Insurance and Reinsurance Companies that was established in Turkey and, insurance and reinsuranc companies were established in foreign countries are inspected and including branches in Turkey insurance laws by external inspection founding and independent external insurance inspecting founding. Principle about Inspection and Reinsurance Companies by Independent External Inspection Founding. In addition to inspection is applied by public or external inspection companies in insurance companies, the inspection is applied by departments inside the company, inspection forms the internal inspection. The scope for forming the internal inspection mechanism is formed by two or less inspectors. Inspectors must have 4 years degree diploma, and their professional area must be, insurance, banking, economics, law, finance, administration or accounting area are observing the insurance sector chosen. In Turkey, ther are no internal inspection department of all companies, ther are public inspection and external inspection in common. Forming internal inspection departments of all companies effects positively the internal inspection activity before the other inspections are related removing the existing problems of company activities. Internal inspection is different from public and independent inspection companies. At the end of the inspections fixed findings are presented to management committee and upper management as a report. In the end of negative results, the upper management committee decides to if there is a punishment. There is signed out the observed subjects by inspectors of insurance companies during inspection ; · Safe Inspection, · Cheque and Voucher Inspectioni · Bank Inspection, · Personal Inspection, · Declaration Inspection, · Social Work Inspection, · Inventory Inspection, · Technical Departments Inspection, · Reinsurance Process Inspection, · Claim Department Inspection, · Expense Inspection, At the end of all these examinations, the main service of insurance is decreasing people's anxiety of undetermined and impossibility of guessing the individual damage in the future. Insurance companies must investigate the premium that are collected from insured people, and must have strong structure about technique and finance. Insurance companies' profits are formed by technical profits are fixed at the end of insurance services and, financial profits that are fixed for investigating the existing funds for increasing financial profits, that means ; they must increase premium income. Public has two main expection from insurance companies. At macro level, contributing economy by canalizing the investigation from insurance companies collected premium. At micro level, protecting the insured people rights and benefits. Insurance companies must not be poor about finance and technique for applying these functions. Companies performances that formed in years appears only in applied inspection. In Turkey Insurance Companies Inspection is applied by mainly Turkish Republic Prime Ministry Insurance Inspections Committee. In addition to inspection that are applied by inspection committee, there are inspection are applied by independent inspection companies in our country and internal inspection that are applied by inspection departments of own structure. Internal inspection activity does not exist in all insurance companies in Turkey. As a result, inspection at insurance companies is very important for being competely economical and social expectation duty from insurance company. Independent External Inspection Companies are not the only inspection, general accepted accounting principles but also it determines the prepared functions the suitability to legal judgements. Accounting to internal inspection, forming the internal inspection department in all insurance companies must be an obligation. Inspection unit must have an information center formed by departments of insurance company, and also prepared report is in the end of the inspections must be established. Thanks to this information center, fixing more active and quick solution must be produced, which departments have the same problems, in which departments there are big problems make company is the responsible for problems. There must be arrengement for punishing, upper management personnel members, general manager, assistant general manager, when the insurance company gets in a poor situation. These arrengements are prepared with respect to the important risk source of management mistakes are removed visually. Insurance Inspection Committee must be more active working, and its authority must be increased. Such that this committee structure must have an information center that collects internal inspection reports of insurance companies and independent external inspection reports and also the other sector reports. When these conditions are provided Insurance Inspection Committee will observe superior insurance companies easily and get necessary precaution on time.
Keywords: SİGORTA ŞİRKETLERİ